The Effect of Work Environment, Work Quality, Emotional Intelligence, and Intellectual Intelligence on Employee Performance at PUDAM Tirta Bina Labuhanbatu Regency - Muksin Kurniawan; Siti Lam'ah Nasution; Abdul Halim (PT Mattawang Mediatama Solution, 2023)
This type of research is quantitative in nature, and the place of implementation of this research is PUDAM Tirta Bina, Labuhanbatu Regency. Data collection techniques used in this study were observation, documentation and questionnaires using a Likert scale. In this study, the population was 110 employees of the Tirta Bina Public Water Supply Company (PUDAM) in Labuhanbatu Regency. Samples were taken using the slovin formula, which was determined or a significance level of 0.05, so the sample size in this study was 86 people. The Fcount value in this study is equal to 37,005 > Ftable 2.48 with a significance value of 0.000 <0.05. From these results, it can be concluded that the Work Environment (X1), Work Quality (X2), Emotional Intelligence (X3) and Intellectual Intelligence (X4) simultaneously have a positive and significant effect on Employee Performance (Y). R Square from the analysis of the coefficient of determination of 0.646 means that Employee Performance (Y) can be explained by the variables Work Environment (X1), Work Quality (X2), Emotional Intelligence (X3) and Intellectual Intelligence (X4) of 64.6%, while the rest is 35.4% can be explained by other variables not examined in this study